The method of forming a decentralized register of events of the information infrastructure of the enterprise - Basinya, Е.А.; Safronov, А.В. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article describes the problems of existing approaches to the collection, processing, and analysis of data from the information and communication sector of the enterprise. The article considers threats of abnormal internal and external influences on its objects and systems. The authors review an original method for forming a decentralized registry of the enterprise information infrastructure events. The scientific novelty of the proposed solution lies in the automatic management of local and network information processes of technical objects based on data from decentralized blockchain storage with a trust management system for recorded events. Decision-making is based on objective and verified information. Another aspect of innovation is the profiling of access to information and the protection of the data transfer process based on group as well as iterative multilayer encryption. The article is a logical continuation of the authors' work on a decentralized approach to the collection and processing of data from the enterprise information infrastructure. The article considers the development and research of the system for detecting, preventing intrusions, and falsifying the event register based on the proposed approach for integration as a module of the system of intelligent adaptive management of the enterprise network infrastructure.